OS09.7.A Quality of life outcomes in patients with incidental and operated meningiomas: the QUALMS study. (9th September 2021) - Keshwara, S M; Islim, A I; Millward, C P; Gillespie, C S; Richardson, G E; Mustafa, M A; George, A M; Mills, S J; Brodbelt, A R; Jenkinson, M D
Abstract: BACKGROUND: Long-term Health-Related Quality of Life (HRQoL) is an important measure of patient wellbeing. There is a paucity of studies evaluating HRQoL in meningioma patients. MATERIAL AND METHODS: Cross-sectional study of adult patients with an incidental or symptomatic intracranial meningioma. Patients with less than 5 years of follow-up, a history of craniospinal radiation or neurofibromatosis type 2 were excluded. HRQoL was evaluated with SF-36, EORTC QLQ-C30 and EORTC QLQ-BN20 questionnaires. Outcome determinants were evaluated using a multi-variable linear regression analysis, adjusted for patient, tumour and treatment characteristics, and duration of follow-up. RESULTS: 699 patients were invited to participate and 246 responded: 118 (48%) had an incidental meningioma. Mean age at diagnosis was 56.8 years (SD=13) and 81% were female. Median time from diagnosis to completion of questionnaire was 8.5 years (IQR 6.8–11.5). During follow-up, 158 patients (64.2%) had at least one operation for their meningioma and 47 patients (19.1%) had radiotherapy. Of those operated, 126 (79.7%) had WHO grade 1 and 24 (15.2%) had grade 2 meningiomas. Compared to normative population values, meningioma patients reported a worse SF-36 general health score (mean 61.9 vs 56.5, P =0.003) but a similar QLQ-C30 global health score (mean 62.3 vs 65.8, P =0.039), worse SF-36 and QLQ-C30 physical functioning scores (mean 74.1 vs 64.6, P <0.001 and mean 81.8 vs 76.5, P =0.007) and similar SF-36 and QLQ-C30 emotional health scores (mean 72.2 vs 70.9, P =0.367 and mean 71.0 vs 71.9, P =0.960). QLQ-C30 cognitive functioning was worse (mean 80.5 vs 71.4, P <0.001). Compared to the meningioma literature, QLQ-BN20 seizure burden was similar (mean 2.0 vs 1.6, P =0.760). A worse performance status at diagnosis was associated with an inferior QLQ-C30 global health score (β-coefficient=-4.9 [95% CI -9.1-(-)0.6] P =0.024). Number of surgeries was significantly associated with a worse QLQ-C30 cognitive functioning score (β-coefficient=-7.0 [95% CI -13.2-(-)0.9], P =0.025). Anti-epileptic drug use was associated with a significantly worse QLQ-C30 emotional health score (β-coefficient=-10.9 [95% CI -21.7-(-)0.01], P =0.050). CONCLUSION: Meningioma patients have long-term HRQoL impairments affecting their physical and cognitive functions. An understanding that multiple surgeries affects cognitive function, and the need for anti-epileptic drugs equate to poorer emotional health, could help target appropriate therapies and support in the future.